Optimizing Seismic Design of Multi-Tower Buildings Using Sky Bridge Isolation and BIM: A Case Study - Michael Loreantz Steven Tambunan; Jessica Sjah; Ayomi Dita Rarasati; Ryan Sulistian; Bambang Trigunarsyah (International Journal of Engineering and Technology Innovation, 2024)
This research aims to extend prior knowledge of sky bridge isolations in a design case study that complies with building codes, focusing on the design of a multi-tower building linked with a sky bridge and its isolation system. Building Information Modeling (BIM) is used during the design process. Linear time history analysis is performed to capture seismic responses without statistical distortion of response combinations. Link elements are used to simulate the isolations, and the ground motions are excited in bidirectional directions. The experimental results demonstrate that using an isolation system at the sky bridge connection improves torsional behavior, as evidenced by a 12% reduction in torsional mass contribution in the fundamental mode shape of the buildings. Other notable improvements include better lateral force distributions and optimization of reinforcement volume by 36.91% at maximum. Additionally, convenient post-design procedures, such as automated design visualizations and quantity surveys of reinforcements are reported through using BIM.